PCR Primer Design for 16S rRNAs for Experimental Horizontal Gene Transfer Test in Escherichia coli - Miyazaki, Kentaro; Sato, Mitsuharu; Tsukuda, Miyuki (Frontiers in Bioengineering and Biotechnology, 2017)
We recently demonstrated that the Escherichia coli ribosome is robust enough to accommodate foreign 16S rRNAs from diverse gamma- and beta-proteobacteria bacteria (Kitahara, Yasutake, and Miyazaki. Proc Natl Acad Sci U S A. 109:19220-19225, 2012, doi: 10.1073/pnas.1213609109). Therein, we used the common universal primers Bac8f and UN1541r to obtain a nearly full-length gene. However, we noticed that these primers overlap variable sites at 19[A/C] and 1527[U/C] in Bac8f and UN1541r, respectively, and thus the amplicon could contain mutations. This is problematic, particularly for the former site, because the 19th nucleotide pairs with the 916th nucleotide, which is a part of the “central pseudoknot” and is critical for function. Therefore, we mutationally investigated the role of the base pair using several 16S rRNAs from gamma- and beta- proteobacteria. We found that both the native base pairs (gammaproteobacterial 19A-916U and betaproteobacterial 19C-916G) and the non-native 19A-916G pair retained function, whereas the non-native 19C-916U was defective 16S rRNAs. We next designed a new primer set, Bac1f and UN1542r, so that they do not overlap the potential mismatch sites. 16S rRNA amplicons obtained from the environmental metagenome using the new primer set were dominated by proteobacterial species (~85%). Subsequent functional screening identified various 16S rRNAs from proteobacteria, all of which contained native 19A-916U or 19C-916G base pairs. The primers developed in this study are thus advantageous for functional characterization of foreign 16S rRNA in E. coli with no artifacts.